Relationship between physical parameters and shooting velocity in elite female rink hockey players - Rosanas-Orra, R.; Altarriba-Bartes, A.; Vicens-Bordas, J.; Merino-Tantiña, J.; Borràs-Boix, X. (Apunts Sports Medicine, 2026)
The aim of this study was to evaluate various physical parameters and their relationship with shooting velocity in female rink hockey players. Eight female players (age: 24.8 ± 3.88 years, body mass: 62.6 ± 4.67 kg, height: 167 ± 0.04 cm) were measured, weighted and tested for thoracic spine range of motion, spine rotational strength, chop, lift, bench press, and handgrip. Shooting velocity of each participant was measured for both slap and backhand shots. Results showed a significant correlation between slap shot velocity and body mass (r = 0.76; p = .02; ICC 0.1338 - 0.9532), spine rotation strength to the right with body weight (r = 0.76; p = .04; ICC 0.0368 - 0.9638) and with 79 % of body weight (r = 0.84; p = .01; 0.2374 - 0.9759). Interestingly, backhand velocity showed a strong correlation and a close to significant p-value with bench press power at 25 kg (r = 0.70; p = .054; ICC -0.0141 - 0.9401), 30 kg (r = 0.53; p = .097; ICC - 0.1415 - 0.9233) and 35 kg (r = 0.63; p = .10; ICC -0,1568 - 0.8596). Similar results were observed with the estimated one repetition maximum for the bench press (r = 0.67; p = .077; ICC -0.0892 - 0.9307). Results suggested that including exercises to strengthen the torso rotation muscles and upper extremity strength could improve shooting velocity in female rink hockey players.